Surface activation of medical grade polyurethane for the covalent immobilization of an anti-adhesive biopolymeric coating - Matinha-Cardoso, J (2021)
Hospital-acquired infections are still a major concern worldwide, being frequently related to bacterial biofilm formation on medical devices, and thus difficult to eradicate with conventional antimicrobial treatments. Therefore, infection-preventive solutions based on natural polymers are being investigated. Recently, a marine cyanobacterium-derived polymeric coating (CyanoCoating) has demonstrated great anti-adhesive potential when immobilized onto gold model substrates. In this work, we took this technology a step closer to an industrial application by covalently immobilizing CyanoCoating onto medical grade polyurethane (PU). This immobilization was developed through the introduction of linkable moieties onto PU inert surface using different pre-treatments. Besides the application of polydopamine (pDA) linker layer, other processes frequently found in industrial settings, as atmospheric plasma (using O2 or N2 as reactive gases) and ozone surface activations, were evaluated. From all the pre-treatments tested, the ozone activation was the most promising since the obtained coating not only revealed a homogeneous distribution, but also significantly reduced the adhesion of two relevant etiological bacteria in static conditions (the Gram-positive Staphylococcus aureus and the Gram-negative Escherichia coli). Moreover, it also impaired E. coli biofilm formation under simulated urinary tract dynamic conditions, reinforcing the potential of CyanoCoating as an antibiotic-free alternative to mitigate medical device-associated infections, particularly in the urinnary tract.